Gene duplication and transposition of mobile elements drive evolution of the Rpv3 resistance locus in grapevine - Foria, Serena; Eisenmann, Birgit (The plant journal, 2020)
A wild grape haplotype (Rpv3-1) confers resistance to Plasmopara viticola. We mapped the causal factor for resistance to an interval containing a TIR-NB-LRR (TNL) gene pair that originated 1.6-2.6 million years ago by a tandem segmental duplication. Transient coexpression of the TNL pair in Vitis vinifera leaves activated pathogen-induced necrosis and reduced sporulation compared with control leaves. Even though transcripts of the TNL pair from the wild haplotype appear to be partially subject to nonsense-mediated mRNA decay, mature mRNA levels in a homozygous resistant genotype were individually higher than the mRNA trace levels observed for the orthologous single-copy TNL in sensitive genotypes. Allelic expression imbalance in a resistant heterozygote confirmed that cis-acting regulatory variation promotes expression in the wild haplotype. The movement of transposable elements had a major impact on the generation of haplotype diversity, altering the DNA context around similar TNL coding sequences and the GC-content in their proximal 5′-intergenic regions. The wild and domesticated haplotypes also diverged in conserved single-copy intergenic DNA, but the highest divergence was observed in intraspecific and not in interspecific comparisons. In this case, introgression breeding did not transgress the genetic boundaries of the domesticated species, because haplotypes present in modern varieties sometimes predate speciation events between wild and cultivated species.
Published online: 30 September 2019
Gesehen am 27.01.2021